1995
DOI: 10.1099/0022-1317-76-7-1815
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent disruption of E2F-p107 complexes by human papillomavirus type 16 E7

Abstract: The human papillomavirus type 16 (HPV-16) E7 and adenovirus (Ad) EIA oncoproteins share a common pathway of transformation. They disrupt the cell cycle G~ phase-specific protein complex containing the E2F transcription factor and the regulatory protein Rbl, the retinoblastoma tumour suppressor gene product. In the G1 and S phases of the cell cycle, E7 and E1A bind two other cellular complexes containing the Rbl-related protein p107 and E2F. Ad E1A disrupts both complexes and releases active E2F. In contrast, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…As yet we do not have an explanation for this e ect, however, a similar, but not identical, situation was observed with papillomavirus E7 protein which was found to dissociate p107 containing complexes only if they did not at the same time carry cyclin A, i.e. E7 dissociated p107 complexes in G 1 but not in S phase (Zerfass et al, 1994). The recent observation (Ikeda and Nevins, 1993) that E1A protein may have two separate functions in its activity towards pocket proteins, one being the capacity to bind the protein, the other one the dissociation of complexes, might be relevant in this regard.…”
Section: Mrc5mentioning
confidence: 69%
“…As yet we do not have an explanation for this e ect, however, a similar, but not identical, situation was observed with papillomavirus E7 protein which was found to dissociate p107 containing complexes only if they did not at the same time carry cyclin A, i.e. E7 dissociated p107 complexes in G 1 but not in S phase (Zerfass et al, 1994). The recent observation (Ikeda and Nevins, 1993) that E1A protein may have two separate functions in its activity towards pocket proteins, one being the capacity to bind the protein, the other one the dissociation of complexes, might be relevant in this regard.…”
Section: Mrc5mentioning
confidence: 69%
“…While Harrington et al showed that Rb, but not p107 and p130, was essential for G 1 control in DNA-damaged mouse embryo fibroblasts (28), others have provided evidence that p107 and/or p130 function in murine cell cycle control following DNA damage (59,63). The mechanism by which E7 inactivates p107 and p130 is not clear and may differ according to cell type (1,4,40,68). In agreement with Jones et al (40), we find that E7 reduces p107 and p130 levels, and we extended these findings to show that the same regions of E7 are required for reducing Rb, p107, and p130 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it binds to the cdk inhibitor proteins p21/WAF1 and p27/Kip1, blocking their binding to cyclins and, in the case of p21, PCNA and disrupting normal cell cycle control [70]. Similar to Rb, the Rb-related protein p107 is also bound by E7, leading to release of E2F transcription factors from p107 in the G1 phase [69]. Furthermore, E7 binds to Mi2β, a member of the histone deacetylase complex which influences the histone-DNA interaction and the access of transcription factors [3], probably leading to deregulation of genes that govern the cell cycle.…”
Section: High-grade Squamous Intraepithelial Lesionsmentioning
confidence: 99%